2011
DOI: 10.1186/1747-1028-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Nek family of kinases in cell cycle, checkpoint control and cancer

Abstract: Early studies in lower Eukaryotes have defined a role for the members of the NimA related kinase (Nek) family of protein kinases in cell cycle control. Expansion of the Nek family throughout evolution has been accompanied by their broader involvement in checkpoint regulation and cilia biology. Moreover, mutations of Nek family members have been identified as drivers behind the development of ciliopathies and cancer. Recent advances in studying the physiological roles of Nek family members utilizing mouse genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 86 publications
2
98
0
Order By: Relevance
“…5A and B). Previous reports showed that NEK kinases, including NEK7, play important roles in the cell-cycle checkpoint regulation at G 1 -S, intra-S, and G 2 -M phases in addition to their established functions during mitosis (39,40), and our results appear to be consistent with these findings. In addition, we prepared cell lysates 24 hours after the release of cell cycle and conducted Western blotting for phosphorylated H3 Serine 10, a maker of mitosis.…”
Section: Direct Regulation Nek7 Transcription By Whsc1supporting
confidence: 93%
See 1 more Smart Citation
“…5A and B). Previous reports showed that NEK kinases, including NEK7, play important roles in the cell-cycle checkpoint regulation at G 1 -S, intra-S, and G 2 -M phases in addition to their established functions during mitosis (39,40), and our results appear to be consistent with these findings. In addition, we prepared cell lysates 24 hours after the release of cell cycle and conducted Western blotting for phosphorylated H3 Serine 10, a maker of mitosis.…”
Section: Direct Regulation Nek7 Transcription By Whsc1supporting
confidence: 93%
“…S4). Among these genes, NEK7 was previously reported to regulate proliferation of cancer cells (36,39), which was a phenotype observed with WHSC1 knockdown. In addition, NEK7 was confirmed to be significantly decreased after knockdown of WHSC1 at the protein level.…”
Section: Direct Regulation Nek7 Transcription By Whsc1mentioning
confidence: 93%
“…Although NEKs have divergent functions, a common feature is their regulation of microtubules (reviewed in Moniz et al [171]). NEK genes have roles in cell cycle regulation as well as ciliagenesis, and it is thought that expansion in organisms with cilia/flagella might be due to the need to coordinate the cell cycle with cilia development [171,172]. In G. lamblia, the NEK family has expanded to an astounding 198 of the 278 protein kinases, 70 per cent of which are likely to be catalytically inactive [37].…”
Section: Gsk3mentioning
confidence: 99%
“…Mutations of NEK family members have also been identified as drivers behind the development of ciliopathies and cancer. Recent emergence of comprehensive cancer genomes is highlighting certain members of the NEK family as targets of frequent mutations (Moniz, Dutt, Haider, & Stambolic, 2011). We also identified five genes in the RNF family: RNF12, RNF181, RNF20, RNF31,RNF7.…”
Section: Prognostic Gene Identificationmentioning
confidence: 94%